RESEARCH AND APPLICATION OF ARTIFICIAL INTELLIGENCE AND COMPUTER VISION TECHNIQUES FOR ASSISTING IN EARLY DETECTION AND DIAGNOSIS OF BREAST CANCER AT NGHE AN ONCOLOGY HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Objectives: To evaluate the efficiency of artificial intelligence (AI) software version 1.2.1 (combining YOLOv7 and ResNet50 algorithms) in assisting the diagnosis, early detection, localization, and classification of breast cancer lesions on mammograms at Nghe An Oncology Hospital.Methods: The study was conducted on 400 DICOM-format mammograms from 200 retrospective patients (from March 2024 to August 2024) and 200 prospective patients (from September 2024 to December 2024). The YOLOv7 model was utilized for lesion detection, while ResNet50 was applied for the detailed classification of masses and microcalcifications. The AI diagnostic results were compared against the histopathological gold standard.Results: In the retrospective phase, the software achieved an accuracy of 94% (188/200 cases) and 100% sensitivity for malignant cases (166/166 cases). In the prospective phase, accuracy reached 91% (182/200 cases) while maintaining 100% sensitivity by correctly identifying all 10 malignant cases, with no critical lesions missed. The inference speed reached 3.6 ms/image. Conclusion: The AI software operates stably, demonstrates high sensitivity, and integrates seamlessly with the PACS system, providing highly effective support for the early detection and screening of breast cancer in clinical practice.
Keywords: Breast cancer; Artificial intelligence; Computer vision; YOLOv7; ResNet50; Mammography.